2016
DOI: 10.3168/jds.2015-9321
|View full text |Cite
|
Sign up to set email alerts
|

Lipid complex effect on fatty acid profile and chemical composition of cow milk and cheese

Abstract: The effect of administration of lipid complex (LC) on cow milk and cheese characteristics was studied. Lipid complex was elaborated based on grapeseed oil with synthesized conjugated linoleic acid (CLA) and Atlantic mackerel oil enriched in n-3 fatty acids. The 4-wk experiment was conducted on 30 Polish Holstein Friesian cows. The experimental group cow diet was supplemented with 400 g/d of LC (containing 38% CLA, and eicosapentaenoic acid + docosahexaenoic acid in a relative amount of 36.5%) on a humic-minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
(60 reference statements)
2
29
0
2
Order By: Relevance
“…milk production, milk and cheese FA profiles) are reported elsewhere (Vargas-Bello-P erez et al, 2015). The use of FO in dairy cow diets has been shown to improve the FA profile of milk and cheese (Allred et al, 2006;Bodkowski et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…milk production, milk and cheese FA profiles) are reported elsewhere (Vargas-Bello-P erez et al, 2015). The use of FO in dairy cow diets has been shown to improve the FA profile of milk and cheese (Allred et al, 2006;Bodkowski et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Coefficients >900 g/kg would reflect an increase and <900 g/kg would reflect a decrease in the presence of individual FA because of enzymatic and microbiological transformations during ripening (Collins et al, 2003;Buccioni et al, 2012;Laskaridis et al, 2013). Previous research has shown that for short periods of ripening, the FA profile of the cheese was similar to that of the original milk (Allred et al, 2006;Bodkowski et al, 2016). However, in agreement with the results of the present study, the FA profile of the long ripened cheeses differed from that of the original milk, as found with Parmesan (Mordenti et al, 2015), Raclette (Bocquel et al, 2016) and Feta (Laskaridis et al, 2013) cheeses, but not Emmental (Gnädig et al, 2004).…”
Section: Cheese Manufacturing and Nutrient Recoverymentioning
confidence: 99%
“…The proportion of milk processed into cheese is growing worldwide (IDF, 2015), and there is interest in assessing the effects of different feeding treatments on cheese quality (Colombari et al, 2001;Angulo et al, 2012) including the FA profile of milk and the derived cheese and the pathways of FA transfer from milk to cheese. Some authors have suggested that the FA profile of fresh cheese reflects that of the milk from which it has been made (Allred et al, 2006;Bodkowski et al, 2016); others (Mordenti et al, 2015;Bocquel et al, 2016) have suggested that alterations to the FA profile probably occur during ripening. However, few studies have specifically addressed the transfer of individual FA from milk to cheese (Cattani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies show that the milk processing and cooking do not influence the CLA concentration in milk by products like such as cheese, butter, and ice cream, and so on. Yearling steers Flax seed oil 0.76 mg/g fat [49] Yearling steers Sunflower seed oil 0.85 mg/g fat [49] Yearling steers Flax seed oil 0.79 mg/g fat [49] Yearling steers Sunflower seed oil 0.86 mg/g fat [49] Charolais × Saler steers Extruded linseed 4% 0.72 mg/g fat [55] Charolais cows Extruded linseed 4% 0.40 mg/g fat [55] Holstein cows Extruded linseed 4% 0.99 mg/g fat [55] Charolais bulls Extruded linseed 4% 0.91 mg/g fat [55] German Holstein, bulls Pasture 17 g/100 g fatty acids [60] German Simmental, bulls Pasture 12 g/100 g fatty acids [60] Wagyu x Limousin, steers whole concentrate 0.12 mg/g fat [5] Charolais steers Grass silage 35 g/100 g fatty acids [61] Holstein calves Megalac 15•9 g/100 g fatty acids [62] Holstein calves Protected lipid supplement 14•5 g/100 g fatty acids [62] Holstein calves Protected lipid supplement 10.1 g/100 g fatty acids [62] Angus × Hereford Finishing diet + soy oil 0.28 mg/g fat [63] Limousin, steers Sunflower oil 134 g/100 g fatty acids [64] Angus steers Concentrate + soy oil (6%) 0.34 mg/g fat [65] Angus steers Concentrate + extruded soybean 0.73 mg/g fat [66] Angus crossbred steers Whole pasture 1.5 mg/g fat [67] Charolais steers Grass based + concentrate 1.1 mg/g fat [68] Wagyu crossbred Barley-based diet 1.7 mg/FA [69] Charolais steers Grass silage whole linseed 36 g/100 g fatty acids [56] Bovine Science -A Key to Sustainable Development prepared from milk produced by diet supplementing with soybean, extruded soybean, soybean, and so on in cows, soybean oils, extruded soybean, olive oil and palm oils, linseed and extruded linseed, and flaxseed meal, flaxseed oil, castor oil and soybean, and so on in goats resulted in stable CLA content [31,[70][71][72].…”
Section: Bio-fortified Cla Milk's Cheese and Buttermentioning
confidence: 99%